Hezbollah's Dual Identity: Navigating Political Engagement and Military Resistance against Israel - Zafar, Sheikh Arslan; Shahzadi, Iqra (Annals of Human and Social Sciences, 2025)
This study explores how Iran’s Islamic Revolutionary Guard Corps (IRGC) backs Hezbollah’s dual role—as a legitimate political party and a military organization—and how this affects Lebanon’s sovereignty, governance, and regional stability. This paper investigates the historical origins, ideological basis, and strategic development of Hezbollah, analyzing how it manages its dual identity within Lebanese politics and the wider Middle Eastern geopolitical environment. Additionally, through the defensive realism theory, the research analyzes Hezbollah's connections with Iran and how its involvement in the region has impacted domestic stability and interactions with international entities. Through a qualitative method, we will interpret its function to balance national cohesion and regional dynamics after interventions in the regional wars based on ideology, which creates challenges for Lebanon's sovereignty due to a lack of institutions. As Hezbollah progresses, its dual identity will continue to play a key role in influencing the future of Lebanon and the surrounding area.